We Really Need to Talk About Session Tickets: A Large-Scale Analysis of Cryptographic Dangers with TLS Session Tickets - Hebrok, Sven Niclas; Nachtigall, Simon; Maehren, Marcel; Erinola, Nurullah; Merget, Robert; Somorovsky, Juraj; Schwenk, Jörg (32nd USENIX Security Symposium)

Security Analysis of the 3MF Data Format - Rossel, Jost; Mladenov, Vladislav; Somorovsky, Juraj (Proceedings of the 26th International Symposium on Research in Attacks, Intrusions and Defenses)

Re-Envisioning Industrial Control Systems Security by Considering Human Factors as a Core Element of Defense-in-Depth - Pottebaum, Jens; Rossel, Jost; Somorovsky, Juraj; Acar, Yasemin; Fahr, René; Arias Cabarcos, Patricia; Bodden, Eric; Gräßler, Iris (2023 IEEE European Symposium on Security and Privacy Workshops (EuroS&PW))
The security of Industrial Control Systems is relevant both for reliable production system operations and for high-quality throughput in terms of manufactured products. Security measures are designed, operated and maintained by different roles along product and production system lifecycles. Defense-in-Depth as a paradigm builds upon the assumption that breaches are unavoidable. The paper at hand provides an analysis of roles, corresponding Human Factors and their relevance for data theft and sabotage attacks. The resulting taxonomy is reflected by an example related to Additive Manufacturing. The results assist in both designing and redesigning Industrial Control System as part of an entire production system so that Defense-in-Depth with regard to Human Factors is built in by design.
Keywords: Defense-in-Depth; Human Factors; Production Engineering; Product Design; Systems Engineering

Poster: Circumventing the GFW with TLS Record Fragmentation - Niere, Niklas; Hebrok, Sven Niclas; Somorovsky, Juraj; Merget, Robert (Proceedings of the 2023 ACM SIGSAC Conference on Computer and Communications Security)
State actors around the world censor the HTTPS protocol to block access to certain websites. While many circumvention strategies utilize the TCP layer only little emphasis has been placed on the analysis of TLS-a complex protocol and integral building block of HTTPS. In contrast to the TCP layer, circumvention methods on the TLS layer do not require root privileges since TLS operates on the application layer. With this proposal, we want to motivate a deeper analysis of TLS in regard to censorship circumvention techniques. To prove the existence of such techniques, we present TLS record fragmentation as a novel circumvention technique and circumvent the Great Firewall of China (GFW) using this technique. We hope that our research fosters collaboration between censorship and TLS researchers.

"I don' know why I check this..." - Investigating Expert Users' Strategies to Detect Email Signature Spoofing Attacks - Mayer, Peter; Poddebniak, Damian; Fischer, Konstantin; Brinkmann, Marcus; Somorovsky, Juraj; Sasse, Angela; Schinzel, Sebastian; Volkamer, Melanie (Eighteenth Symposium on Usable Privacy and Security (SOUPS 2022))

TLS-Anvil: Adapting Combinatorial Testing for TLS Libraries - Maehren, Marcel; Nieting, Philipp; Hebrok, Sven Niclas; Merget, Robert; Somorovsky, Juraj; Schwenk, Jörg (31st USENIX Security Symposium (USENIX Security 22))

ALPACA: Application Layer Protocol Confusion - Analyzing and Mitigating Cracks in TLS Authentication - Brinkmann, Marcus; Dresen, Christian; Merget, Robert; Poddebniak, Damian; Müller, Jens; Somorovsky, Juraj; Schwenk, Jörg; Schinzel, Sebastian (30th USENIX Security Symposium (USENIX Security 21))

Raccoon Attack: Finding and Exploiting Most-Significant-Bit-Oracles in TLS-DH(E) - Merget, Robert; Brinkmann, Marcus; Aviram, Nimrod; Somorovsky, Juraj; Mittmann, Johannes; Schwenk, Jörg (30th USENIX Security Symposium (USENIX Security 21))

Analysis of DTLS Implementations Using Protocol State Fuzzing - Fiterau-Brostean, Paul; Jonsson, Bengt; Merget, Robert; de Ruiter, Joeri; Sagonas, Konstantinos; Somorovsky, Juraj (29th USENIX Security Symposium (USENIX Security 20))

Mitigation of Attacks on Email End-to-End Encryption - Schwenk, Jörg; Brinkmann, Marcus; Poddebniak, Damian; Müller, Jens; Somorovsky, Juraj; Schinzel, Sebastian (Proceedings of the 2020 ACM SIGSAC Conference on Computer and Communications Security)
OpenPGP and S/MIME are two major standards for securing email communication introduced in the early 1990s. Three recent classes of attacks exploit weak cipher modes (EFAIL Malleability Gadgets, or EFAIL-MG), the flexibility of the MIME email structure (EFAIL Direct Exfiltration, or EFAIL-DE), and the Reply action of the email client (REPLY attacks). Although all three break message confidentiality by using standardized email features, only EFAIL-MG has been mitigated in IETF standards with the introduction of AEAD algorithms. So far, no uniform and reliable countermeasures have been adopted by email clients to prevent EFAIL-DE and REPLY attacks. Instead, email clients implement a variety of different ad-hoc countermeasures which are only partially effective, cause interoperability problems, and fragment the secure email ecosystem.We present the first generic countermeasure against both REPLY and EFAIL-DE attacks by checking the decryption context including SMTP headers and MIME structure during decryption. The decryption context is encoded into a string DC and used as Associated Data (AD) in the AEAD encryption. Thus the proposed solution seamlessly extends the EFAIL-MG countermeasures. The decryption context changes whenever an attacker alters the email source code in a critical way, for example, if the attacker changes the MIME structure or adds a new Reply-To header. The proposed solution does not cause any interoperability problems and legacy emails can still be decrypted. We evaluate our approach by implementing the decryption contexts in Thunderbird/Enigmail and by verifying their correct functionality after the email has been transported over all major email providers, including Gmail and iCloud Mail.
Keywords: decryption contexts; EFAIL; OpenPGP; S/MIME; AEAD

"Johnny, you are fired!" -- Spoofing OpenPGP and S/MIME Signatures in Emails - Müller, Jens; Brinkmann, Marcus; Poddebniak, Damian; Böck, Hanno; Schinzel, Sebastian; Somorovsky, Juraj; Schwenk, Jörg (28th USENIX Security Symposium (USENIX Security 19))

Scalable Scanning and Automatic Classification of TLS Padding Oracle Vulnerabilities - Merget, Robert; Somorovsky, Juraj; Aviram, Nimrod; Young, Craig; Fliegenschmidt, Janis; Schwenk, Jörg; Shavitt, Yuval (28th USENIX Security Symposium (USENIX Security 19))

Security Analysis of XAdES Validation in the CEF Digital Signature Services (DSS) - Engelbertz, Nils; Mladenov, Vladislav; Somorovsky, Juraj; Herring, David; Erinola, Nurullah; Schwenk, Jörg (Open Identity Summit 2019)

Prime and Prejudice: Primality Testing Under Adversarial Conditions - Albrecht, Martin R.; Massimo, Jake; Paterson, Kenneth G.; Somorovsky, Juraj (Proceedings of the 2018 ACM SIGSAC Conference on Computer and Communications Security)

Attacking Deterministic Signature Schemes Using Fault Attacks - Poddebniak, Damian; Somorovsky, Juraj; Schinzel, Sebastian; Lochter, Manfred; Rosler, Paul (2018 IEEE European Symposium on Security and Privacy (EuroS&P))

On The (In-)Security Of JavaScript Object Signing And Encryption - Detering, Dennis; Somorovsky, Juraj; Mainka, Christian; Mladenov, Vladislav; Schwenk, Jörg (Proceedings of the 1st Reversing and Offensive-oriented Trends Symposium on - ROOTS)

Efail: Breaking S/MIME and OpenPGP Email Encryption using Exfiltration Channels - Poddebniak, Damian; Dresen, Christian; Müller, Jens; Ising, Fabian; Schinzel, Sebastian; Friedberger, Simon; Somorovsky, Juraj; Schwenk, Jörg (27th USENIX Security Symposium (USENIX Security 18))

Return Of Bleichenbacher\textquoterights Oracle Threat (ROBOT) - Böck, Hanno; Somorovsky, Juraj; Young, Craig (27th USENIX Security Symposium (USENIX Security 18))

Security Analysis of eIDAS -- The Cross-Country Authentication Scheme in Europe - Engelbertz, Nils; Erinola, Nurullah; Herring, David; Somorovsky, Juraj; Mladenov, Vladislav; Schwenk, Jörg (12th USENIX Workshop on Offensive Technologies (WOOT 18))

SoK: Exploiting Network Printers - Muller, Jens; Mladenov, Vladislav; Somorovsky, Juraj; Schwenk, Jörg (2017 IEEE Symposium on Security and Privacy (SP))

Breaking and Fixing Gridcoin - Grothe, Martin; Niemann, Tobias; Somorovsky, Juraj; Schwenk, Jörg (11th USENIX Workshop on Offensive Technologies (WOOT 17))

Systematic Fuzzing and Testing of TLS Libraries - Somorovsky, Juraj (Proceedings of the 2016 ACM SIGSAC Conference on Computer and Communications Security - CCS'16)

DROWN: Breaking TLS Using SSLv2 - Aviram, Nimrod; Schinzel, Sebastian; Somorovsky, Juraj; Heninger, Nadia; Dankel, Maik; Steube, Jens; Valenta, Luke; Adrian, David; Halderman, J. Alex; Dukhovni, Viktor; Käsper, Emilia; Cohney, Shaanan; et al. (25th USENIX Security Symposium (USENIX Security 16))

Nonce-Disrespecting Adversaries: Practical Forgery Attacks on GCM in TLS - Böck, Hanno; Zauner, Aaron; Devlin, Sean; Somorovsky, Juraj; Jovanovic, Philipp (10th USENIX Workshop on Offensive Technologies (WOOT 16))

On the Security of TLS 1.3 and QUIC Against Weaknesses in PKCS#1 v1.5 Encryption - Jager, Tibor; Schwenk, Jörg; Somorovsky, Juraj (Proceedings of the 22nd ACM SIGSAC Conference on Computer and Communications Security - CCS '15)

Not so Smart: On Smart TV Apps - Niemietz, Marcus; Somorovsky, Juraj; Mainka, Christian; Schwenk, Jorg (International Workshop on Secure Internet of Things (SIoT))

How to Break XML Encryption -- Automatically - Kupser, Dennis; Mainka, Christian; Schwenk, Jö; Somorovsky, Juraj (9th USENIX Workshop on Offensive Technologies (WOOT 15))

Revisiting SSL/TLS Implementations: New Bleichenbacher Side Channels and Attacks - Meyer, Christopher; Somorovsky, Juraj; Weiss, Eugen; Schwenk, Jörg; Schinzel, Sebastian; Tews, Erik (23rd USENIX Security Symposium (USENIX Security 14))

A New Approach towards DoS Penetration Testing on Web Services - Falkenberg, Andreas; Mainka, Christian; Somorovsky, Juraj; Schwenk, Jörg (2013 IEEE 20th International Conference on Web Services)

One Bad Apple: Backwards Compatibility Attacks on State-of-the-Art Cryptography - Jager, Tibor; Paterson, Kenneth G.; Somorovsky, Juraj (20th Annual Network and Distributed System Security Symposium, NDSS 2013, San Diego, California, USA, February 24-27, 2013)

On Breaking SAML: Be Whoever You Want to Be - Somorovsky, Juraj; Mayer, Andreas; Schwenk, Jörg; Kampmann, Marco; Jensen, Meiko (Presented as part of the 21st USENIX Security Symposium (USENIX Security 12))

Technical Analysis of Countermeasures against Attack on XML Encryption -- or -- Just Another Motivation for Authenticated Encryption - Somorovsky, Juraj; Schwenk, Jörg (2012 IEEE Eighth World Congress on Services)

Sec2: Secure Mobile Solution for Distributed Public Cloud Storages - Somorovsky, Juraj; Meyer, Christopher; Tran, Thang; Sbeiti, Mohamad; Schwenk, Jörg; Wietfeld, Christian

All your clouds are belong to us: security analysis of cloud management interfaces - Somorovsky, Juraj; Heiderich, Mario; Jensen, Meiko; Schwenk, Jörg; Gruschka, Nils; Lo Iacono, Luigi (Proceedings of the 3rd ACM workshop on Cloud computing security workshop - CCSW '11)

On the effectiveness of XML Schema validation for countering XML Signature Wrapping attacks - Jensen, Meiko; Meyer, Christopher; Somorovsky, Juraj; Schwenk, Jörg (2011 1st International Workshop on Securing Services on the Cloud (IWSSC))

How to break XML encryption - Jager, Tibor; Somorovsky, Juraj (Proceedings of the 18th ACM conference on Computer and communications security - CCS '11)

Sec2: Ein mobiles Nutzer-kontrolliertes Sicherheitskonzept für Cloud-Storage - Meyer, Christopher; Somorovsky, Juraj; Driessen, Benedikt; Schwenk, Jörg; Tran, Thang; Wietfeld, Christian

Streaming-Based Verification of XML Signatures in SOAP Messages - Somorovsky, Juraj; Jensen, Meiko; Schwenk, Jörg (2010 6th World Congress on Services)